Efficient Functionalization of Additives at Supramolecular Material Surfaces. Issue 5 (29th November 2016) - Goor, Olga J. G. M.; Keizer, Henk M.; Bruinen, Anne L.; Schmitz, Moniek G. J.; Versteegen, Ron M.; Janssen, Henk M.; Heeren, Ron M. A.; Dankers, Patricia Y. W.
Abstract : Selective surface modification reactions can be performed on additives that are supramolecularly incorporated into supramolecular materials. Hereby, processing of the material, that regularly requires harsh processing conditions (i.e., the use of organic solvents and/or high temperatures), and functionalization can be decoupled. Moreover, high‐resolution depth profiling by time‐of‐flight (ToF) secondary‐ion mass spectrometry clearly shows distinct differences in surface and bulk material composition.